Front-line erlotinib in unselected patients with advanced NSCLC and poor performance status - the TOPICAL study - Karachaliou, Niki; Wei, Jia; Marques, Ana Daniela; Rosell, Rafael (Translational Lung Cancer Research, 2012)
Lung cancer has long been recognized as an extremely heterogeneous disease since its development, in terms of clinical characterizations, prognosis, response and tolerance to treatment, is unique in every patient. Eastern Cooperative Oncology Group performance status (ECOG PS) is the most important predictor of outcome in advanced non-small-cell lung cancer (NSCLC). Patients with PS ≥2 tend to tolerate treatment poorly and have significantly inferior survival compared with patients with PS 0 to 1 (1).